2016
DOI: 10.1073/pnas.1605334113
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants linked to education predict longevity

Abstract: Educational attainment is associated with many health outcomes, including longevity. It is also known to be substantially heritable. Here, we used data from three large genetic epidemiology cohort studies (Generation Scotland, n = ∼17,000; UK Biobank, n = ∼115,000; and the Estonian Biobank, n = ∼6,000) to test whether education-linked genetic variants can predict lifespan length. We did so by using cohort members' polygenic profile score for education to predict their parents' longevity. Across the three cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(67 citation statements)
references
References 59 publications
5
62
0
Order By: Relevance
“…Existing observational studies, however, are likely to be confounded by unobserved factors, such as genetic (12) or other unobserved behavioral and familial factors, that affect both parental education and child health. The presence of such confounding in observational studies was recently demonstrated in a large cross-comparative study showing the similarity in the effect size of paternal and maternal education on child malnutrition (4).…”
Section: Education and Health: Time To Understand And Test The Mechanmentioning
confidence: 99%
“…Existing observational studies, however, are likely to be confounded by unobserved factors, such as genetic (12) or other unobserved behavioral and familial factors, that affect both parental education and child health. The presence of such confounding in observational studies was recently demonstrated in a large cross-comparative study showing the similarity in the effect size of paternal and maternal education on child malnutrition (4).…”
Section: Education and Health: Time To Understand And Test The Mechanmentioning
confidence: 99%
“…The exact strength of the correlation between genetically influenced characteristics of children and the parenting they experience, however, is still uncertain due to the sometimes problematic assumptions of twin studies, while candidate gene studies are limited to examining a narrow range of genes and often have the limitation that they do not replicate in other samples. An increasing number of studies have used genes of children to explain a phenotype in their parents (Joshi et al., ; Marioni et al., ), and molecular genetic evidence is needed to estimate the proportion of the variance the rGEs explain of the parental responses. This can be done by utilizing genome‐wide complex trait analysis with restricted maximum likelihood (GCTA‐GREML; Yang, Lee, Goddard, & Visscher, ; Yang, Lee, Wray, Goddard, & Visscher, ), indicating whether two unrelated individuals are more similar in the parenting they experience because they share the same genes.…”
Section: Introductionmentioning
confidence: 99%
“…This finding, that mortality selection may lead to attenuation, has also been observed in the context of Mendelian randomization. 5,6 If certain genetic profiles are associated with increased risks for mortality, 38,39 then individuals with such genotypes are less likely to be observed in older samples (e.g. Figure 4).…”
Section: Discussionmentioning
confidence: 99%